RELIGIOUS TOLERANCE POLICY IN UZBEKISTAN: HISTORICAL EXPERIENCE, LEGAL FOUNDATIONS, AND ITS ROLE IN ENSURING SOCIAL STABILITY (World Conference on Social Sciences, Law and Public Policy, 2026)
This thesis analyzes the historical roots, constitutional and legal foundations, and institutional mechanisms of the policy of religious tolerance in Uzbekistan. The role of guaranteeing freedom of conscience, strengthening an atmosphere of mutual respect between different religious denominations, scientifically studying the religious and educational heritage, and combating ignorance and extremism with enlightenment in ensuring the stability of society is highlighted. The article also puts forward scientific and practical proposals for developing a culture of religious tolerance in the context of globalization and the digital information space.
Keywords: religious tolerance, freedom of conscience, interfaith dialogue, secular state, legal guarantee, enlightenment, religious heritage, civil solidarity, social stability.